The Impact of Demographic Indicators on Cybersecurity Behaviour of E-Commerce Users in South Africa - Mberikwazvo, Weston Zorodzai (University of the Witwatersrand, Johannesburg, 2024)
This study aims to explore the cybersecurity behaviour of e-commerce users in South Africa, utilising a conceptual framework derived from some elements of both the Health Belief Model (HBM) and the Protection Motivation Theory (PMT). The study investigates the impact of demographic indicators specifically age, gender, and educational level impact the cybersecurity behaviour seeking to understand and contribute to the understanding of cybersecurity practices in response to perceived cyberthreats. A sample of 316 participants was used for the study which varied across different genders, age groups and educational levels. An online survey making use of a questionnaire was used to gather responses to the different dimensions making up cybersecurity behaviour guided by the established conceptual framework. The responses were statistically analysed to establish any patterns and trends using techniques such as correlation analysis and factor analysis. Analysis of the dataset concluded that there was significant difference to the cybersecurity behaviour of e-commerce users in South Africa for each of the demographic indicators of educational level, gender, and age and thus the null hypothesis was rejected for all three factors. Also, the null hypothesis was rejected for a combination of all three demographic indicators and cybersecurity behaviour indicating that a significant difference exists. The results showed that participants in the 36 to 40 years age group showed the highest cybersecurity behaviour level, with the 18 to 20 years and the over 60 years age group showing the lowest. Females showed a lower cybersecurity level in comparison to males with the non-binary participants scoring the lowest. The cybersecurity level increased in general with the educational level of the participants. In a nutshell, the results show that in the context of South African e-commerce users customised interventions based on the educational level, gender, and age need to be considered
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Cybersecurity; Cybersecurity Behaviour; E-commerce; E-commerce Users; Demographic Indicators; Age; Gender; Education Level; UCTD; South Africa; SDG-8: Decent work and economic growth